2008
DOI: 10.1109/tc.2007.70822
|View full text |Cite
|
Sign up to set email alerts
|

Low-Complexity Bit-Parallel Square Root Computation over GF(2^{m}) for All Trinomials

Abstract: In this contribution we introduce a low-complexity bit-parallel algorithm for computing square roots over binary extension fields. Our proposed method can be applied for any type of irreducible polynomials. We derive explicit formulae for the space and time complexities associated to the square root operator when working with binary extension fields generated using irreducible trinomials. We show that for those finite fields, it is possible to compute the square root of an arbitrary field element with equal or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…be of degree ≤ n/2 . From the explicit formulae for a classical implementation by Rodríguez-Henríquez et al [21] we obtain the following.…”
Section: Optimizing F 2 -Linear Operations and Minimal Edge Coloringsmentioning
confidence: 99%
See 1 more Smart Citation
“…be of degree ≤ n/2 . From the explicit formulae for a classical implementation by Rodríguez-Henríquez et al [21] we obtain the following.…”
Section: Optimizing F 2 -Linear Operations and Minimal Edge Coloringsmentioning
confidence: 99%
“…Let A := a 0 + a 1 x + · · · + a n−1 x n−1 be a representative of an F 2 n -element a. In [21] explicit expressions for computing the representations of a 2 and √ a from a 0 , . .…”
Section: Optimizing F 2 -Linear Operations and Minimal Edge Coloringsmentioning
confidence: 99%
“…However, in the case that the irreducible polynomial P (x) is a trinomial, P (x) = x m + x n + 1 with m an odd prime number, then the square root of an arbitrary element A ∈ F 2 m can be obtained at a very low price: the computation of some few additions and shift operations [15]. 5 Furthermore, Rodríguez-Henríquez et al showed in [22] that for all practical cases, the cost of computing in hardware the square root over binary fields generated with irreducible trinomials, is not more expensive than the computational effort required for computing field squarings.…”
Section: B Square Rootmentioning
confidence: 99%
“…Square root can be implemented with fewer resources than squaring if the irreducible is a trinomial [20]. Hence, it might be possible to reduce the complexity of a repeated squaring (especially, varying exponent with the second solution) by, first, "shooting over" the required exponent e with an e opt chain and, then, reversing back with (repeated) square roots, rather than using fewer e opt 's and then reaching e with a few repeated squarings.…”
Section: Future Researchmentioning
confidence: 99%